INTEGRASI ILMU TAUHID SEBAGAI FONDASI FILOSOFIS DALAM SISTEM PENDIDIKAN KARAKTER - Bayu Bambang Nurfauji; Eka Rachmawati; Nizar Sajad Mubarok; Ujen Jaelani; Inun Komalasari (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The science of monotheism is the main foundation in Islamic teachings which discuss the oneness of Allah SWT and his relationship with humans and the universe. In the context of education, the science of monotheism has a strategic role as a basis for values, morals and learning goals. This article aims to examine the relationship between monotheism and education by referring to several classical and contemporary books and literature. The method used is a literature study with a descriptive-analytical approach. The results of the research show that the integration of monotheistic knowledge in education is able to form the  character of students who are faithful, have noble character, and have a balance between intellectual, spiritual and social intelligence. The integration of the science of tawhid into the educational curriculum Is not merely an addition of cognitive content, but rather a transformation of the educational paradigm centered on lillāh (for the sake of Allah). Tawhid functions as a moral regulator (ethics) and a source of meaning for every discipline of knowledge. The implementation of tawhid in education has been proven to shape the holistic character of learners, namely individuals who possess strong faith and noble moral character